STUDY OF PROBIOTIC AND TURMERIC SUPPLEMENTATION ON GROWTH PERFORMANCE AND ECONOMIC ANALYSIS OF THE ETAWA CROSSBREED GOAT - N. L. G., BUDIARI; PUJIAWATI, Y.; KERTAWIRAWAN, I P. A.; Budiana, I N. (Majalah Ilmiah Peternakan, 2022)
Feed additive has been used widely to improve productivity performance by improving feed digestibility and maintaining animal’s health. This study evaluates two types of feed additives in the form of probiotics and turmeric and their combination on growth performance and economic analysis in the etawa crossbreed goat. This study was carried out in the Matahari farmer group, Candi Kuning Village, Tabanan District, Bali Province, from June to Oc- tober 2020. The study used a completely randomized design (CRD) with four treatments, and each treatment used four male etawa crossbreed goats with an average initial weight of 15 kg. The treatments tested were P0: control (forage+0,5 kg/head/day), P1: P0+probiotic-turmeric 5 ml/head/day, P2: P0+probiotic-turmeric 10ml/head/day, P3: P0+probiotic-turmeric 15 ml/head/day. Parameters observed were daily weight gain, feed intake, dry matter digestibility, organic matter digestibility, feed conversion ratio, and economic analysis. Observation data were anal- yzed using analysis of variance and a further test of orthogonal polynomials. To determine the feasibility level of farming, it is carried out by analyzing the Revenue Cost Ratio (R/C ratio). The probiotic and turmeric combination to 15 ml/head/day did not affect the dry matter and organic matter intake. The addition of probiotic turmeric im- proves the dry matter, and organic matter digestibility also reduces the feed conversion ratio. The use of 15 ml of probiotic-turmeric showed the greatest body weight gain and an R/C value of 1.10.